The letters of Hannah Dennison, 1820 settler, 1820-1847 - Edgecombe, Dorothy Ruth (Rhodes University, Faculty of Humanities, Department of History, 1968)
In 1959, the late Miss M.G. Masson of Salem, at the instigation of Mrs. Dorothy Rivett-Carnac, presented a bundle of Gush family papers to the Cory Library. Among these papers was a series of letters written by Hannah Dennison, who came to South Africa in 1820, as a member of Carton's party from Nottinghamshire. This thesis offers a transcription of the letters together with editorial comment, and the letters from the main source for a reconstruction of the life and attitudes of a most enterprising woman.
Keywords: Dennison, Hannah Elizabeth, 1791-1850 -- Correspondence; British settlers of 1820 (South Africa) -- Correspondence; Cape of Good Hope (South Africa) -- History -- 1814-1852; Women -- South Africa; British settlers of 1820 (South Africa); Women -- South Africa -- Correspondence